Protective effect of hawthorn vitexin on the ethanol-injured DNA of BRL-3A hepatocytes. Issue 50 (17th December 2021) - Ding, Chengshi; Shen, Henglun; Tian, Zhongjing; Kang, Meiling; Ma, Jing; He, Qing; Wang, Jinglong; Zhang, Yingxia; Deng, Yanmei; Wang, Deya
Abstract : Abstract: Vitexin is a natural active ingredient in hawthorn leaves, which has a wide range of anti-tumor effects. This study was conducted to assess the protective effect of hawthorn vitexin on the ethanol-injured DNA of hepatocytes in vitro and to explore its mechanism. The effect of different concentrations of hawthorn vitexin on ethanol-injured hepatocytes was detected via the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide method to study the protective effect of hawthorn vitexin on ethanol-injured DNA damage in hepatocytes. Single-cell gel electrophoresis was used to observe the effect of hawthorn vitexin on ethanol-induced DNA damage in hepatocytes, and the Olive tail moment was measured. Cell physiological and biochemical indexes, such as superoxide dismutase activity, malonaldehyde content, and glutathione peroxidase activity, were detected with kits. The mRNA expression of the superoxide dismutase gene was measured via real-time quantitative polymerase chain reaction. It was showed that 0.2, 0.4, and 0.8 mg mL −1 hawthorn vitexin could significantly repair hepatocyte growth and ethanol-induced DNA damage. This effect was closely related to the improvement in superoxide dismutase, malonaldehyde, and glutathione peroxidase. Hawthorn vitexin could be used to repair ethanol-injured hepatocytes through antioxidation effects, and showed potential for the treatment of liver injury.